Aprendendo a ser médico: análise da relação trabalho - saúde de médicos residentes - Silva, Monalisa Vasconcelos Ernesto (2013)
This paper analyses the relation between the process of Medical Residence (MR) and the health of the resident doctors. Intending both capacitating and actualizing, the MR has a fundamental role to the new graduate doctor. Through the MR, he will gains experience and knowledge that will be reflected further in better opportunities of job as well as in the professional clinic itself. The choose for researching in this particular academic field dues to the interest in analyze the possible health implications suffered by these new doctors as a consequence of their professional activities during the MR. Thus, this study has as the main objective to analyze the established relations between the doctor´s health during the MR and as specific objectives to investigate the syllabus and the peculiarities of the resident doctor activity; to delineate the conditions and organization of the resident doctor activity; to identify the sources of the sufferings and pleasures of their work; to analyze in which way these professionals manage both private and professional lives; to explore the peculiar duality established by MR`s doctor concerning being both a professional and a student, and, finally, to identify and to analyze healthy problems as illness, accidents and sufferings pointing out possible solutions to the problems. The theoretical basis of this paper will be supported by the academic fields of Work Psychodynamics; Ergonomy of Activity and Clinics of Activity. To the purpose of this study, 29 resident doctors of a university hospital, residents of the second year and from different clinical areas were investigated. It was used pre-structured application forms to investigate the objectives stated before. The analysis of the collected data followed a thematic content analysis. The results reveal that the lack of material to both preservation and recuperation of the patient´s health is a reflection of the working condition these professionals are submitted. The resident doctors also pointed as a source of suffering their impotence face the public health service including the lack of working structure and the excessive hours of working. As the principal source for pleasure they pointed the satisfaction in helping the patients. Thus, in this context, the notion of risk is part of the process of MR, including occupational, professional and psychosocial ones. It was also noticed that the private life of these professionals were banished to a second place. The family has to deal with the distance and the absence of them, facing the hard working schedule and the extra work in other institutions. Not forgetting that the new doctor is yet a student and so he has to deal with the limits imposed by the medical practice as well as by the adviser doctor. Thus, the principal problems suffered by the resident doctors detected by this research were: physical and psychiatric stress, sleeping and hormonal alterations, inadequate food and lack of disposition to the practice of physical activities which implies in the diminution of life quality. In the other hand, some of the participants denied any sort of health problems caused by the MR. In spite of all the situation presented above, the results also appointed a significant equilibrium, being perceived as fundamental, but transient.